Maternal history and uterine artery wave form in the prediction of early-onset and late-onset preeclampsia: A cohort study - Nidhi Sharma; Krishnamurthy Jayashree; Kulasekaran Nadhamuni (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Pregnancy induced hypertension (PIH) is a significant cause of maternal morbidity and mortality. Pregnancy-induced-hypertension can be prevented by identification of prenatal and antenatal factors. The uterine artery Doppler waveform transforms into a high flow with low resistance at 22-24 wk. Objective: To study the maternal risk factors and uterine artery Doppler waveform in singleton mid-trimester pregnancy and predict the occurrence of pregnancy-induced hypertension. Materials and Methods: This is a cohort study comprising of Doppler ultrasound examination of the uterine arteries at 20-23 wk gestation in 697 women with singleton pregnancies attending a routine target scan. The pregnant women were followed up. PIH was recorded in 57 (8.18%) of all pregnancies. Results: Maternal age >34 yr, primiparity, the presence of chronic hypertension was also associated with increased risk of PIH. High pulsatility index (>95th percentile) as compared to low pulsatility index was a good tool for the detection of PIH (sensitivity 91.23% and specificity 99.06%, p<0.05). Presence of high pulsatility was a significant risk factor for early-onset PIH as compared to late-onset PIH. Conclusion: Uterine artery Doppler can be safely performed at the time of routine target anomaly scan in the second trimester. It is simple, economical, feasible and with good detection rates.